Gamifikasi Bahasa Arab dengan Model Blended Learning - Eka Lutfiyatun (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2021)
Arabic learning in Indonesia is entering a new phase during the pandemic. Students are allowed to join limited face-to-face meetings with reduced class hours. In response to this, a blended learning model is applied by combining face-to-face learning models in class and at other times conducting online learning outside the classroom or at home. To help students achieve the objectives of learning Arabic, gamification of learning is needed by utilizing online or android-based games. This study aims to describe how educators apply gamification in blended learning. The method used in writing this article is descriptive analysis or literature review which produces descriptive data from various research results on teacher experiences of gamification in blended learning. The results of this study indicate that students can practice with the educational games provided. This provides easy access and efficiency and enhances student interest.